Earnings prospects, matching effects, and the decision to terminate a criminal career - Pezzin, Liliana E. (Journal of quantitative criminology, 1995)
This study represents an effort to investigate the age pattern of criminal involvement from an economist's perspective. It presents a dynamic stochastic model of sequential search and match evaluation which is used to explain the reasons for, and the timing of, the decision to terminate a criminal career. The behavioral implications derived from the theoretical model are tested using individual National Longitudinal Survey of Youth data. Estimation results strongly support the prediction of a negative relation between the option value of retaining a criminal career and desistance decisions. More specifically, the effects of current and future expected criminal earnings are shown to be negative, substantial, and statistically significant in determining desistance probabilities. Retiring behavior is also significantly responsive to variables measuring personal costs of punishment and the availability and attractiveness of a legal income-generating activity in ways consistent with theoretical expectations.